Analysis and design of a reconfigurable wideband I/Q modulator and Ultra-Wideband I/Q demodulator for multi-standard applications. (August 2020) - Mansour, Marwa; Zekry, Abdelhalim; Ali, Mohammed K.; Shawkey, Heba
Abstract: This work presents an Ultra-Wideband (UWB) in-phase/quadrature (I/Q) demodulator, and a reconfigurable wideband (I/Q) modulator using 130 ​nm CMOS process for multi-standard applications. The proposed designs are suitable for multi-band or wideband LTE RF transceiver. Both the RF stage in the demodulator, and the IF stage in the modulator are implemented using Capacitive Cross Coupling (CCC) common-gate configuration to enhance bandwidth and increase gain at a moderate power consumption. Furthermore, the reconfigurability of the modulator is achieved by matching the RF port by means of a high coupling wideband five ports transformer and a bank of switched capacitors for proper channel selection. The demodulator consumes 10.5 ​mW from a 1.2 ​V supply and it has conversion gain (CG) of 10 ​dB with 3-dB bandwidth of 9 ​GHz (1–10 ​GHz). The demodulator input 1-dB compression point (P1dB) is −4.15 dBm at 4.5 ​GHz, and the LO-to-RF isolation is better than −45 dB due to compact and fully symmetrical layout where the active area is 0.22 m m 2 . The modulator demonstrates a CG of 6.8 ​± ​1.5 ​dB in the frequency band 1.5–4 ​GHz, where the maximum CG equals 8.32 ​dB ​at LO power of 3 dBm, and output 1 ​dB compression point (OP_1 ​dB) equals −1.6 dBm. Also, the LO suppression and the harmonic suppression in the modulator are less than −50 ​dBc, and −60 ​dBc, respectively. The modulator active area is 0.55 m m 2 and its power consumption is 16.6 ​mW from a 1.2 ​V supply.